Combining solubilization and controlled release strategies to prepare pH-sensitive solid dispersion loaded with albendazole: in vitro and in vivo studies - Dehai Su; Mingyang Bai; Chaoqun Wei; Xiangyang Long; Xuezhen Liu; Xiangguang Shen; Huanzhong Ding (Frontiers in Veterinary Science)
Albendazole (ABZ), classified as a class II basic drug under the Biopharmaceutics Classification System (BCS), is widely recognized for its therapeutic efficacy in treating and preventing trichuriasis. However, despite its clinical relevance, ABZ’s oral administration presents challenges due to its poor solubility and pH sensitivity, which diminish its therapeutic effectiveness. Additionally, high dosing regimens of ABZ pose risks of developmental toxicity in animal models. This study developed a pH-sensitive solid dispersion of albendazole (ABZ-pHs-SD) using Glyceryl Monostearate (GM) in conjunction with Hypromellose Acetate Succinate (HPMC-AS). Characterization via Scanning Electron Microscopy (SEM), Powder X-ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), and Fourier Transform Infrared Spectroscopy (FT-IR) confirmed the high dispersion of ABZ in a crystalline state within the carrier. Furthermore, we compared the in vitro dissolution profile, pharmacokinetics, and intestinal drug concentration of ABZ-pHs-SD with commercially available formulations. Our findings demonstrated that ABZ-pHs-SD exhibited an excellent dissolution profile, significantly increasing the solubility of ABZ in water by 3.15 times. The formulation effectively prevented drug release in acidic environments while maintaining a slow release in weakly alkaline conditions. Additionally, compared to commercial formulations, ABZ-pHs-SD showed significantly lower Cmax (4.70 ± 1.16 vs. 6.83 ± 0.66 μg/mL) and higher Tmax (5.5 ± 0.93 vs. 3.75 ± 0.71 h) in vivo, achieving elevated drug concentration levels in the cecal and colonic environments (p < 0.01) without significantly decreasing bioavailability. Overall, our research findings indicate that ABZ-pHs-SD serves as a promising drug delivery strategy for the poorly soluble and pH-sensitive ABZ. Particularly, the simple preparation of solid dispersion demonstrates strong industrial feasibility.